1998
DOI: 10.3171/jns.1998.88.3.0457
|View full text |Cite
|
Sign up to set email alerts
|

“Threshold-level” multipulse transcranial electrical stimulation of motor cortex for intraoperative monitoring of spinal motor tracts: description of method and comparison to somatosensory evoked potential monitoring

Abstract: This novel method for intraoperative monitoring of spinal motor conduction appears to meet all of the goals outlined above. Although the risk of postoperative motor deficit is relatively low for the majority of spine surgeries (for example, a simple disc), high-risk procedures, such as tumor resection, correction of vascular abnormalities, and correction of major deformities, should benefit from the virtually immediate and accurate knowledge of spinal motor conduction provided by this new monitoring approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
124
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(136 citation statements)
references
References 45 publications
11
124
0
1
Order By: Relevance
“…Of lower-limb muscles, AbH is typically the first-recruited using threshold-level repetitive transcranial electrical stimulation of motor cortex in the anesthetized patient during spine surgery. 11,37 Thresholds for recruiting this muscle with single-pulse transcranial magnetic stimulation in awake, neurologically intact subjects are typically equal to or lower than those for other lower-limb muscles. 10 In persons with incomplete cervical spinal cord injurymost of whom had been injured at least 1 year prior to testing -we showed that AbH was significantly more likely to be recruited by TMS than other lower-limb muscles, including hamstring, tibialis anterior, and soleus.…”
Section: Discussionmentioning
confidence: 99%
“…Of lower-limb muscles, AbH is typically the first-recruited using threshold-level repetitive transcranial electrical stimulation of motor cortex in the anesthetized patient during spine surgery. 11,37 Thresholds for recruiting this muscle with single-pulse transcranial magnetic stimulation in awake, neurologically intact subjects are typically equal to or lower than those for other lower-limb muscles. 10 In persons with incomplete cervical spinal cord injurymost of whom had been injured at least 1 year prior to testing -we showed that AbH was significantly more likely to be recruited by TMS than other lower-limb muscles, including hamstring, tibialis anterior, and soleus.…”
Section: Discussionmentioning
confidence: 99%
“…The higher sensitivity (relative to SEPs) of MEPs to spinal cord dysfunction is consistent with previous reports. [11][12][13][14] There were no false negative SEPs or MEPs but 6 (75%) false-positive SEPs and 13 (65%) false-positive MEPs.…”
Section: Discussionmentioning
confidence: 99%
“…36 Furthermore, MEPs may be more sensitive to ischemia than SSEPs and less likely to deteriorate after midline myelotomy, unlike SSEPs. 4,5,7,10,12,24,[34][35][36]40 Also, as demonstrated in this case, not only will MEPs often be present in neurologically compromised patients, 9 but they may also be able to detect subclinical deficits, 3,23,38 whereas SSEPs are significantly more likely to be absent in the normal and compromised neurological states. In a recent prospective trial, 38.7% of patients undergoing a variety of spinal procedures had either significantly diminished or absent tibial SSEPs.…”
Section: Discussionmentioning
confidence: 89%